Out-of-pocket expenses experienced by rural Western Australians diagnosed with cancer - Newton, J.; Johnson, C.; Hohnen, H.; Bulsara, M.; Ives, A.; McKiernan, S.; Platt, V.; McConigley, Ruth; Slavova-Azmanova, N.; Saunders, C. (Springer, 2018)
© 2018 Springer-Verlag GmbH Germany, part of Springer Nature Purpose: Out-of-pocket expenses (OOPE) can have a significant impact on patients’ experiences of cancer treatment. This cross-sectional study sought to quantify the OOPEs experienced by rural cancer patients in Western Australia (WA), and determine factors that contributed to higher OOPE. Methods: Four hundred people diagnosed with breast, lung, colorectal or prostate cancer who resided in selected rural regions of WA were recruited through the WA Cancer Registry and contacted at least 3 months after diagnosis to report the medical OOPE (such as surgery or chemotherapy, supportive care, medication and tests) and non-medical OOPE (such as travel costs, new clothing and utilities) they had experienced as a result of accessing and receiving treatment. Bootstrapped t tests identified demographic, financial and treatment-related factors to include in multivariate analysis, performed using log-linked generalised linear models with gamma distribution. Results: After a median 21 weeks post-diagnosis, participants experienced an average OOPE of AU$2179 (bootstrapped 95% confidence interval $1873–$2518), and 45 (11%) spent more than 10% of their household income on these expenses. Participants likely to experience higher total OOPE were younger than 65 years (p = 0.008), resided outside the South West region (p = 0.007) and had private health insurance (PHI) (p < 0.001). Conclusions: Rural WA cancer patients experience significant OOPE following their diagnosis. The impact these expenses have on patient wellbeing and their treatment decisions need to be further explored.